2014
DOI: 10.1370/afm.1641
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular Risk and Statin Use in the United States

Abstract: PURPOSE Statins reduce the risk of mortality and coronary artery disease in individuals at high cardiovascular risk. Using nationally representative data, we examined the relationships between statin use and cardiovascular risk, diagnosis of hyperlipidemia, and other risk factors. METHODSWe analyzed data from the 2010 Medical Expenditure Panel Survey, a nationally representative survey of the US civilian noninstitutionalized population. The study sample had a total of 16,712 individuals aged 30 to 79 years. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
51
2
1

Year Published

2016
2016
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(59 citation statements)
references
References 35 publications
5
51
2
1
Order By: Relevance
“…295 Similarly, in the US Medical Expenditure Survey, statin therapy was being used in 2010 by 58% of people aged 30-79 years with coronary artery disease and by 52% of those aged over 40 years with diabetes. 296 In the UK, analyses of the Clinical Practice Research Datalink in 2014-15 indicated that statin therapy had been started by only about 60% of patients who had recently had a first cardiovascular event and by about 25% of patients in whom a 10 year cardiovascular risk ≥20% had been recorded by the General Practitioner within the past month. 297 A study in Denmark found that negative statin-related news stories were repeatedly followed by average proportional increases of about 10% in the likelihood of stopping statin therapy.…”
Section: Public Health Consequences Of Misleading Claims About the Samentioning
confidence: 99%
“…295 Similarly, in the US Medical Expenditure Survey, statin therapy was being used in 2010 by 58% of people aged 30-79 years with coronary artery disease and by 52% of those aged over 40 years with diabetes. 296 In the UK, analyses of the Clinical Practice Research Datalink in 2014-15 indicated that statin therapy had been started by only about 60% of patients who had recently had a first cardiovascular event and by about 25% of patients in whom a 10 year cardiovascular risk ≥20% had been recorded by the General Practitioner within the past month. 297 A study in Denmark found that negative statin-related news stories were repeatedly followed by average proportional increases of about 10% in the likelihood of stopping statin therapy.…”
Section: Public Health Consequences Of Misleading Claims About the Samentioning
confidence: 99%
“…In summary, the results of these reviews indicate that the prognosis of women with abdominal aortic aneurysm is worse than that of men; although, we have not considered the management of cardiovascular risk (often worse in women), 42,43 complications after repair, and longer term quality or length of life. Women have smaller aortas than men, 44 and perhaps if a smaller threshold for both diagnosis and intervention were introduced, compared with those recommended for men, women might have a better chance of being offered and surviving intervention at a younger age.…”
Section: Schermerhorn Et Al (2012) 30mentioning
confidence: 99%
“…In addition, some studies reported that the ACC/AHA guidelines improved the alignment of statin eligibility 5, 32, 33. Recently, Ko et al 27.…”
Section: Discussionmentioning
confidence: 99%